Effect of Glycyrrhizin glabra in nutrient on sexual desire and semen parameters of bulls born in Iraq during winter: AL-Badry, K.I.1, AL-Ani, A.2 and Ibrahim,F.F. - البدري, كريم عويد (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study is to investigate the sexual desire and semen characteristics of Friesian bulls born in Iraq by adding different concentration of Glycyrrhizin glabra to nutrient of these bulls and study the interaction between months and these treatments. Nine bulls divided randomly to three equal groups ,first group control T1 ,second and third group T2 ,T3 adding 200,400 mg/ kg body weight of Glycyrrhizin glabra respect .Sexual desire was measured according to reaction time and ejaculates collection by artificial vagina and examined using the following parameters: volume, mass, individual motility ,dead and abnormal sperm , concentration of sperms`/ml and total number of sperms , during December, January and February. Results revealed that the treatment T3 showed significant (P < 0.05) superior sexual desire and some semen characteristics in most month of this study comparative with treatment T2 and control , but treatment T2 it is didn’t appear to causes deleterious changes in reproductive performance of this bulls . Results also indicated that best (P < 0.05) sexual desire was in February and best (P < 0.05) some semen parameters were in January and February